Design4Health Melbourne 2017 - Seemann, Kurt; Barron, Deirdre (Swinburne University of Technology, 2017)
Design4Health is an international conference that brings together designers, health professionals and creative practitioners with researchers, clinicians, policy makers and users from across the world to discuss, disseminate and test their approaches and methods in the ever-changing nexus between design and health. The conference hosted a series of different events that provided an active forum to explore how the disciplines of design and health might intersect to bring forth new ways of thinking and working in what is a dynamic, innovative and increasingly important area of research and practice. The central question has been: How can we work together to achieve positive and sustainable impact on the social, economic and cultural factors within our communities and beyond? The range and insights presented at the D4HMelbourne event has revealed both the enormous value of this movement in research, and the benefits from undertaking serious, applied, and critical efforts that design and health expertise generate when they come together.
Design4Health, Melbourne. Proceedings of the Fourth International Conference on Design4Health 2017, Melbourne Cricket Ground, 4 - 7 Dec 2017, Melbourne, Victoria, Australia